Subjective executive function weaknesses are linked to elevated internalizing symptoms among community adolescents - Mullin, Benjamin C. (Assessment, 2018)
Adolescence is a period of high risk for the emergence of problems with anxiety and depression. Theory and research suggest that executive function deficits accompany internalizing and externalizing problems, although more evidence is required to understand these relationships. This study employed a commonly used rating scale of executive function, the Brief Rating Inventory of Executive Function (BRIEF), and examined relationships with self- and parent-reported internalizing and externalizing problems among a community sample of 299 adolescents. The sample was 56.2% female, with a mean age of 16.22 years old (SD = 2.36 years). Analyses revealed strong associations between poorer self- and parent-reported executive function skills and the severity of anxiety and depression symptoms. Problems with executive function were also associated with externalizing symptoms. These results indicate that subjective ratings of executive function capture important aspects of cognitive problems that are highly relevant to adolescent psychopathology in a transdiagnostic fashion.